Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 1178 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Melanerpes formicivorus (Swainson, 1827)", "Country is Colombia", "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 1178 records from 25 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0026053-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences